AN ANALYSIS OF SECURITY AND SERVICE QUALITY TOWARD PURCHASE DECISION ON E-COMMERCE AND ITS IMPLICATIONS OF CONSUMER LOYALTY - -, Ardiansyah (Prosiding International conference on Information Technology and Business (ICITB), 2015)
In the marketing world, especially through internetmarketing or what is known as e-commerce, an e-marketercannot ignore the role of the online shop as a medium fortheir marketing communications, where marketingactivities via e-commerce is currently being favorable bythe people in Indonesia. However transaction through ecommercehas the fairly high riskpotential. Therefore thefactor of security and service quality become a benchmarkon purchasing decisions through e-commerce. The purposeof this study is to analyzewhether security factordirectlyinfluences purchasing decisions through e-commerce,service quality factor directly influences purchasingdecisions through e-commerce, security and service qualityfactor directly influences purchasing decisions through ecommerce,as well as security and service qualityfactorgives significant effect on e-commerce consumer loyalty.This research was conducted by taking samples of ecommerceusers in Indonesiawhich were most active topurchase online products or services in 2014.KEYWORDS: E-commerce, Security, ServiceQuality, Purchasing Decisions, Loyalty